Application of Practicum-Based Learning with Video Media to Improve Basic Learning Outcomes for Class X Students of Vocational High School - Susilowati (JTP - Jurnal Teknologi Pendidikan, 2023)
This study aims to apply practicum-based learning and video media to improve basic boga learning outcomes in class X students of VHS 6 Surabaya. The subjects of this study were students of class X Tata Boga VHS 6 Surabaya in the 2021/2022 academic year, totaling 36 students. This study used a classroom action research design with two cycles. Data collection techniques were carried out by literature study and observation. The data that has been collected is then analyzed thematically. The results showed that the application of practicum-based learning with video media was able to improve student learning outcomes in the first cycle by 36.1% while the second cycle was 77.8%, which means that there was an increase in the KKM score by 41.7%, this means that the Application of Practicum-Based Learning with video media can improve the learning outcomes of basic boga subjects for class X VHS 6 students by 41.7%. So it can be concluded that video-based practicum can improve student learning outcomes. This method can be an effective alternative to improve student learning outcomes, especially in subjects that require direct practicum.